Analysis of Oil Palm Farming in the Padaelo Farmers Group in Bantuas Village, Palaran District, Samarinda City - Humairo Aziza; Helena Helena; Rossy Mirasari; Sri Ngapiyatun; Ahmad Zamroni; Andi Lisnawti (Jurnal Loupe, 2025)
Oil palm is a commodity with relatively high productivity compared to other plantation commodities. However, increasing the scale of oil palm farming is not always in line with improving farmers' welfare. Some of the factors that are suspected of influencing include high production costs, unstable selling prices of FFB that do not benefit farmers, limited market access, and weaknesses in farming management and management. This study aims to analyze the production costs, receipts, and income of farmers who are members of the Padaelo Farmers Group. The research was carried out for 4 months with a case study approach and descriptive quantitative methods. The sampling technique uses a saturated census, which is as many as 25 people. The data consists of primary and secondary data. The average area of oil palm land owned by farmers is 1.64 ha/person with a plant age of 18 years. The average production reaches 645 kg/ha/one harvest and the selling price is Rp1,800 /kg. The results of the study show that in one harvest, the production cost incurred by farmers reaches Rp327,482/ha and the income obtained is Rp1,161,000/ha, so that the income received is Rp833,518/ha.